大腸直腸癌の予後を判定する方法 (2016)
本明細書において、ａ）被験体からの腫瘍組織試料の腫瘍区画パネルで、マーカーパネルの各マーカーの発現レベルを決定することと、ここで該マーカーパネルは、ＴＥＭ１、ＨＩＦ２α、ＣＡＩＸ、ＰＤＧＦＲβ、フィブロネクチン、コラーゲンＩ、コラーゲンＩＶ及びＣＤ３１のうちの少なくとも２つを含み、該腫瘍区画パネルは、純粋な間質、腫瘍、間質血管及び腫瘍血管の少なくとも３つの腫瘍区画を含み、ｂ）該被験体のＴＡＰＰＳスコアを決定することと、ｃ）被験体のＴＡＰＰＳスコアと大腸直腸癌と診断された被験体の母集団のＴＡＰＰＳスコアを比較することとによって、大腸直腸癌と診断された被験体が大腸直腸癌を再発するリスクを決定する方法、並びに大腸直腸癌と診断された被験体の臨床転帰を予測する方法が、開示される。また、関連するコンピュータで実行される方法及びシステム、キット並びに腫瘍マイクロアレイも開示される。 Provided herein are methods for determining the risk that a subject diagnosed with colorectal cancer will develop a recurrence of colorectal cancer and methods of predicting clinical outcome for a subject diagnosed with colorectal cancer by a) determining the level of expression for each marker of a panel of markers in a panel of tumor compartments in a tumor tissue sample from the subject, wherein the panel of markers comprises at least two of TEM1, HIF2α, CAIX, PDGFRβ, fibronectin, collagen I, collagen IV, and CD31 and wherein the panel of tumor compartments comprises at least three tumor compartments of pure stroma, tumor, stromal vessel, and tumor vessel; b) determining the TAPPS score for said subject; and c) comparing the TAPPS score of the subject to the TAPPS score of a population of subjects diagnosed with colorectal cancer. Also provided are related computer-implemented methods and systems, kits, and tumor microarrays.